The Protective Effect of Liquiritin in Hypoxia/Reoxygenation-Induced Disruption on Blood Brain Barrier - Li, Mengting; Ke, Jia; Deng, Yiqing; Chen, Chunxiang; Huang, Yichen; Bian, Yuefeng; Guo, Shufen; Wu, Yang; Zhang, Hong; Liu, Mingyuan; Han, Yan (Frontiers in Pharmacology, 2021)
Background: Stroke is the second leading cause of death in human life health, but current treatment strategies are limited to thrombolytic therapy, and because of the tight time window, many contraindications, and only a very small number of people can benefit from it, new therapeutic strategies are needed to solve this problem. As a physical barrier between the central nervous system and blood, the blood-brain barrier (BBB) maintains the homeostasis of the central nervous system. Maintaining the integrity of the BBB may emerge as a new therapeutic strategy. Liquiritin (LQ) is a flavonoid isolated from the medicinal plant Glycyrrhiza uralensis, and this study aimed to investigate the protective effects of LQ on brain microvascular endothelial cells (BMECs), to provide a new therapeutic strategy for stroke treatment, and also to provide research ideas for the development of traditional Chinese medicine (TCM). Methods: The protective effects of LQ on BMECs under the treatment of hypoxia reoxygenation (H/R) were investigated from different aspects by establishing a model of H/R injury to mimic ischemia-reperfusion in vivo while administrating different concentrations of LQ, which includes: cell proliferation, migration, angiogenesis, mitochondrial membrane potential as well as apoptosis. Meanwhile, the mechanism of LQ to protect the integrity of BBB by antioxidation and inhibiting endoplasmic reticulum stress was also investigated. Finally, to search for possible targets of LQ, we employed a proteomic analysis approach. Results: LQ can promote cell proliferation, migration as well as angiogenesis and reduce mitochondrial membrane potential damage and apoptosis. Meanwhile, LQ can also reduce the expression of related adhesion molecules, and decrease the production of reactive oxygen species. In terms of mechanism study, we demonstrated that LQ could activate Keap1 / Nrf2 antioxidant pathway, inhibit endoplasmic reticulum stress, and maintain the integrity of blood-brain barrier. Through differential protein analysis, we also found 5 disease associated proteins. Conclusion: Studies have shown that LQ can promote cell proliferation, migration as well as angiogenesis, and reduce cell apoptosis, which may be related to its inhibition of oxidative and endoplasmic reticulum stress, and then maintain the blood-brain barrier. Future studies will revolve around the 5 differential proteins.